One or many project offices in educational organization of tertiary education: advantages and disadvantages - A. I. Gromova; P. V. Pavlovsky (Вестник университета)
The article is devoted to the creating and management expediency of several project offices in an educational organization of tertiary education (hereinafter – OTE). The topic relevance is due to the growing number and types of ongoing projects that require proper organization and management and, consequently, governance of project management offices. The article presents the features of educational projects and the role of the project management office in the OTE system. The main types of project management offices at universities and their functions and tasks are described. Common elements of successful project management offices from around the world are highlighted based on a global study conducted by the Project Management Institute (PMI) together with PricewaterhouseCoopers (PwC) in 2021. The advantages and disadvantages of creating a single system of several project offices of different orientation and a single project management office at the university are discussed. Based on the information from the scientific literature and the conducted research, the authors conclude that in order to use all the advantages of the project office in full, it is necessary to create one project office in OTE. However, the authors also claim the need for further research to assess the feasibility of the practical implementation of their proposed solution.